Tourismpreneurship: Local Wisdom-Based Innovation And Market Expansion For Silver Jewelry In Bali - Sang Ayu Putu Shinta Setia Dewi; Bagus Putu Wahyu Nirmala; Putu Wibby Prasetya (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2026)
The creative economy industry, particularly the craft and fashion sectors, continues to show positive growth in Bali as a world tourism center. This study aims to analyze product development strategies and market expansion of silver jewelry SMEs facing global challenges and digital disruption. The object of this research is Atma Silver Jewelry, which innovated through the "Luwih Jewelry" product line. Using a descriptive qualitative approach with data collection through documentation of business proposals, financial reports, and observation of marketing activities, the study finds that innovation based on Balinese cultural wisdom (Tri Hita Karana) and feminine aesthetics successfully meets the needs of the modern market. Furthermore, the implementation of digital marketing through social media and marketplaces, as well as collaboration with influencers, has succeeded in expanding the market reach internationally. Consequently, this business model not only generates profit but also empowers local artisans in Celuk Village and supports sustainable business practices.